Malignant peripheral nerve sheath tumor in a patient without neurofibromatosis 1 (NF1): a rare case of primary lung location - Grzywa-Celińska, Anna; Szmygin-Milanowska, Katarzyna; Emeryk-Maksymiuk, Justyna; Walczyna, Maria; Palonka, Michał; Krusiński, Adam; Siwiec, Jan (Journal of Education, Health and Sport, 2018)
We present a rare case of a patient operated due to a lung tumor, which was ultimately diagnosed as malignant peripherial nerve sheath tumor (MPNST). MPNSTs are rare tumors of soft tissue with mesenchymal origin. The World Health Organization has distinguished this group in order to unify terms in mesenchymal heterogeneous malignant tumors, e.g. neurofibrosarcomas, malignant schwannomas and malignant neurilemmoma [1]. They can occur as a result of neoplastic expansion of peripheral nerves’ branches, peripheral nerve fibers’ sheaths or Schwann cells, although many researchers believe that these tumors can derive not only from one, but several cell lines. MPNSTs are very rare in thorax, where they show aggressive pattern of growth [2] and stem from pleural cells rather than lung tissue.